2020
DOI: 10.1155/2020/3607414
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Recovery in Mental Illness: The Perspectives of Patients, Caregivers, and Community Members in Dar es Salaam, Tanzania

Abstract: Background. Promoting mental health and care in the community setting leads to the recovery of patients with mental illness. Although recovery in mental health is a complex phenomenon, caregivers and community members have important roles to play in the recovery process for patients with mental illness. Little is documented on how recovery is promoted in the community setting. This study explored the experience of patients, caregivers, and community members on how recovery can be realized in a patient with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
(48 reference statements)
3
10
0
Order By: Relevance
“…Additional barriers, including seeking mental health services from traditional and faith healers, the lack of need for treatments, or the high cost of medications, were described as barriers to mental health policy implementation in the hospital. The results of this study were relevant to the previous studies carried out in Tanzania which reported how traditional healers have charged too much for their services for treating mental disorders (Muela et al, 2012;Mwansisya et al, 2015;Rugema et al, 2015;Ali and Agyapong, 2020;Blixen et al, 2020;Iseselo and Ambikile, 2020).…”
Section: Discussionsupporting
confidence: 66%
“…Additional barriers, including seeking mental health services from traditional and faith healers, the lack of need for treatments, or the high cost of medications, were described as barriers to mental health policy implementation in the hospital. The results of this study were relevant to the previous studies carried out in Tanzania which reported how traditional healers have charged too much for their services for treating mental disorders (Muela et al, 2012;Mwansisya et al, 2015;Rugema et al, 2015;Ali and Agyapong, 2020;Blixen et al, 2020;Iseselo and Ambikile, 2020).…”
Section: Discussionsupporting
confidence: 66%
“…1 It is recognised that effective prevention and treatment of mental illness options do exist. 5 In recognising this, the Government of Tanzania intentionally provides mental illness treatment services free of charge. Contrarily, there are many people with serious mental illnesses in the country but they do not attend treatment.…”
Section: Introductionmentioning
confidence: 99%
“…15 Formal treatments are treatments offered by trained professionals who utilise available resources to provide evidence-based treatments to people with mental illness. 5 Being unaware of mental illness is the leading reason for disconnection between actual treatment and careseeking tendency which, consequently makes people withdraw from seeking mental health services ordrop out the mental health service. 3 The perception that mental illness is caused by supernatural powers is not the only barrier to formal mental health utilisation in Zanzibar, accessibility of mental health services in the region is also a contributing factor.…”
Section: Introductionmentioning
confidence: 99%
“…However, it could also be that the experience of burden as a consequence of caring for an individual with schizophrenia leads to a worse family environment. In this regard, other studies have shown that dissatisfaction with family support is linked to caregiver burden and relapse in people with schizophrenia [ 16 , 19 , 20 ]. The present study adds to the growing literature about family functioning as a potential target for treatment that aims to improve schizophrenia outcomes and reduce caregiver burden.…”
Section: Discussionmentioning
confidence: 98%
“…Considerable work is needed to elucidate specific factors that influence the extent of caregiver burden to recommend culturally appropriate areas for supportive interventions. Studies conducted in urban Tanzania found that poor family and social support are significant determinants for relapse in schizophrenia [ 19 , 20 ]. A better understanding of these factors can have important implications for the caregiver’s well-being as well as for the recovery and overall quality of life of the individual living with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%